Preconception midwifery care for women of reproductive age - Annisa Rusdi; Arifa Mirandra; Laila Laila (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Preconception care is an essential strategy to improve women's health status before pregnancy to prevent maternal and neonatal complications. Purpose: to describe the implementation of midwifery care during the preconception period among women of reproductive age. Method: This research used a case study design with a continuity-of-care approach, involving four clients (Ms. F, Ms. I, Ms. M, and Ms. L) selected through purposive sampling. Results: Variations in preconception health status, ranging from optimal conditions to the presence of risk factors such as hypertension, obesity, and chronic energy deficiency. The care provided included health screening, education, lifestyle modification, blood pressure control, stress management, nutritional improvement, supplementation, and immunization. Evaluation indicated improvements in knowledge and positive behavioral changes toward healthier lifestyles, although some risk factors still required ongoing monitoring. Conclusion: In conclusion, comprehensive, continuous preconception midwifery care plays an important role in improving women's physical, psychological, and social readiness before pregnancy. Suggestion: Strengthening preconception services through screening and early detection of risk factors is necessary to achieve healthy and high-quality pregnancies.